ANALISIS KUALITAS AIR PADA KERAMBA BUDIDAYA IKAN BANDENG (Chanos chanos) DI PERAIRAN LABORATORIUM SLAMARAN PEKALONGAN - Juita Sihombing; Nanda Riskyana; Benny Diah Madusari; M. Zulkham Yahya (Bapelitbang Kabupaten Batang, 2022)
ABSTRACT Milkfish (C. chanos) cultivation with cage ponds is one of the alternative aquaculture activities that can be developed in coastal areas. The purpose of this study was to determine the water quality condition in the cultivation of milkfish (C. chanos) using the cage method in the waters of the Slamaran Laboratory, Pekalongan. This research was conducted at the Brackish and Marine Water Laboratory, Faculty of Fisheries, Pekalongan University, Krapyak Lor Village, Pekalongan City by observing the physical and chemical parameters of water during one cycle of fish cultivation. Based on the measurement results of water quality parameters, the pH value was 7, temperature 31.4oC, DO 20 mg/l, ammonia 0.15 mg/l, phosphate 0.03 mg/l, nitrite 0 mg/l, nitrate 2 mg/l and salinity. 11 ppt. The condition of the water quality parameters during the fish farming period runs stably. The water quality parameter values ​​also tend to be good when analyzed based on the results of related studies. So that the conclusions that can be conveyed from the results of this study are that the condition of water quality in milkfish (C. chanos) cultivation activities in the cage ponds of the Slamaran Pekalongan Laboratory based on analysis and literature study is still quite good and feasible to be used as a fish cultivation rearing.